2016
DOI: 10.3354/dao03054
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel delivery via moist pellets to treat monogenean parasites of yellowtail kingfish Seriola lalandi: efficacy and feed acceptance

Abstract: Praziquantel (PZQ) is registered for oral use against Benedenia seriolae infecting Seriola spp. in Japan, but its bitter taste causes poor palatability. Incorporating PZQ in a moist pellet may help mask the flavor to improve intake. Altering delivery, however, may influence efficacy. We assessed the minimum effective concentrations of PZQ in moist pellets delivered by intubation for the monogeneans Zeuxapta seriolae and B. seriolae infecting yellowtail kingfish Seriola lalandi in flow-through tanks. The optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…Parasitised animals may have decreased appetites ( Sitjà-Bobadilla et al, 2006 ), feeding hierarchies may exist ( McCarthy et al, 1992 ), or the feed may be unappealing ( Yamamoto et al, 2011 ). PZQ has a bitter taste, with low palatability, and there have been several reports of problems pertaining to feed rejection, vomiting and reduced feed intake in several fish species ( Sitjà-Bobadilla et al, 2006 ; Williams et al, 2007 ; Yamamoto et al, 2011 ; Forwood et al, 2013a , 2016b ; Partridge et al, 2014 ). This can be a significant issue, Yamamoto et al (2011) reported up to a 95% reduction in feed intake in chub mackerel Scomber japonicus when PZQ was added to feed pellets at a PZQ dose of 150 mg/kg (dietary inclusion level of 0.5%; S.Shirakashi unpublished), and low palatability of medicated feed has resulted in variations in efficacy and occasions where high treatment doses are ineffective at removing parasites from various fish species ( Hirazawa et al, 2004 ; Sitjà-Bobadilla et al, 2006 ; Williams et al, 2007 , 2009 ).…”
Section: Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Parasitised animals may have decreased appetites ( Sitjà-Bobadilla et al, 2006 ), feeding hierarchies may exist ( McCarthy et al, 1992 ), or the feed may be unappealing ( Yamamoto et al, 2011 ). PZQ has a bitter taste, with low palatability, and there have been several reports of problems pertaining to feed rejection, vomiting and reduced feed intake in several fish species ( Sitjà-Bobadilla et al, 2006 ; Williams et al, 2007 ; Yamamoto et al, 2011 ; Forwood et al, 2013a , 2016b ; Partridge et al, 2014 ). This can be a significant issue, Yamamoto et al (2011) reported up to a 95% reduction in feed intake in chub mackerel Scomber japonicus when PZQ was added to feed pellets at a PZQ dose of 150 mg/kg (dietary inclusion level of 0.5%; S.Shirakashi unpublished), and low palatability of medicated feed has resulted in variations in efficacy and occasions where high treatment doses are ineffective at removing parasites from various fish species ( Hirazawa et al, 2004 ; Sitjà-Bobadilla et al, 2006 ; Williams et al, 2007 , 2009 ).…”
Section: Deliverymentioning
confidence: 99%
“…Lowering the PZQ dose (allowing for lower dietary inclusion levels) and extending feed times has been trialled with some success in Seriola spp. and spotted halibut Verasper variegatus ( Hirazawa et al, 2004 ; Williams et al, 2007 ; Partridge et al, 2014 ), as has withholding feed for a period before treatment ( Pool et al, 1984 ; Forwood et al, 2016b ); however, denying food is less than ideal when trying to achieve maximum growth of fish ( Yamamoto et al, 2011 ).…”
Section: Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, masking with attractants, such as freshly coated garlic extract, aided overcome the bitterness of PZQ diets in yellowtail amberjack (Pilmer, 2016), while included dietary PZQ microcapsules increased the palatability of the medicated diet but at the same time reduced the bioavailability of the drug in the circulation of the same fish species (Partridge et al, 2014). Intubation with PZQ was proved effective against B. seriolae (Williams et al, 2007;Forwood et al, 2016), but this administration route is unfortunately an impractical approach for the treatment of a sick stock containing numerous animals. (Ogawa & Yokoyama, 1998;Hirazawa et al, 2004;Yamamoto et al, 2011).…”
Section: Monogeneans (Skin Flukes)mentioning
confidence: 99%
“…Cestodes, such as the beef tapeworm, Taenia saginata, and the pork tapeworm, Taenia solium, are also susceptible to PZQ [34]. There are also veterinary uses of the drug -for example in fish farming, companion animals and agriculture [35][36][37][38]. Interestingly, there is also a considerable "grey literature" on the use of PZQ to clear ornamental fish tanks etc of infestation by planarians and other worms.…”
Section: Treatment Of Schistosomiasismentioning
confidence: 99%